2017
DOI: 10.1016/j.ekir.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Regular or Extended Hemodialysis and Hemodialfiltration on Plasma Oxalate Concentrations in Patients With End-Stage Renal Disease

Abstract: IntroductionCalcium oxalate supersaturation is regularly exceeded in the plasma of patients with end-stage renal disease (ESRD). Previous reports have indicated that hemodialfiltration (HDF) lowers elevated plasma oxalate (POx) concentrations more effectively compared with hemodialysis (HD). We reevaluate the therapeutic strategy for optimized POx reduction with advanced dialysis equipment and provide data on the effect of extended treatment time on dialytic oxalate kinetics.MethodsFourteen patients with ESRD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 40 publications
(73 reference statements)
2
24
1
2
Order By: Relevance
“…They reported a 71% decrease in mean plasma oxalate during a single, high‐flux dialysis session. In 2017, Ermer et al reported 90% intradialytic reduction in plasma oxalate levels, with no significant differences between standard hemodialfiltration, extended hemodialfiltration, and HD . It has been postulated that if calcium oxalate precipitates are formed during the interdialytic period, such precipitates may dissolve post‐HD and oxalosis does not ensue, as long as the post‐HD plasma oxalate is <30 mmol/L .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported a 71% decrease in mean plasma oxalate during a single, high‐flux dialysis session. In 2017, Ermer et al reported 90% intradialytic reduction in plasma oxalate levels, with no significant differences between standard hemodialfiltration, extended hemodialfiltration, and HD . It has been postulated that if calcium oxalate precipitates are formed during the interdialytic period, such precipitates may dissolve post‐HD and oxalosis does not ensue, as long as the post‐HD plasma oxalate is <30 mmol/L .…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Ermer et al reported 90% intradialytic reduction in plasma oxalate levels, with no significant differences between standard hemodialfiltration, extended hemodialfiltration, and HD. 22 It has been postulated that if calcium oxalate precipitates are formed during the interdialytic period, such precipitates may dissolve post-HD and oxalosis does not ensue, as long as the post-HD plasma oxalate is <30 mmol/L. 21 Majority of documented reports of oxalate deposition are from patients who self-medicated large doses of vitamin C (1-2 g per day) and were on older forms of dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Usage of a 96-well plate for measurement of oxalate oxidase activity led to lower values for intra-and interassay variability than previously described. 19 The mean coefficient of variation (CV) was 2% for within-run variation and 4%…”
Section: Measurement Of P Ox and S Ox Concentrationsmentioning
confidence: 99%
“…The lower limit of detection was determined at 2 mM and validated by the accuracy of both ion chromatography and the oxalate oxidase assay. 19 All measurements less than 2 mM were set to 1.9 mM.…”
Section: Measurement Of P Ox and S Ox Concentrationsmentioning
confidence: 99%
“…При порушенні гомеостазу оксалатів відбувається їх накопичення у тканинах організму [35]. Відображення цього процесу фіксується підвищенням концентрації оксалатів у плазмі крові та сечі [36]. Порушення обміну ЩК та збільшення її продукції в крові та сечі поділяються на первинні (генетично зумовлені) та вторинні.…”
Section: таблиця 2 продукти з високим вмістом оксалатівunclassified